2022
DOI: 10.13057/biodiv/d230840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spacing on growth, carbon sequestration, and wood quality of 8-year-old clonal teak plantation for sustainable forest teak management in Java Monsoon Forest, Indonesia

Abstract: Abstract. Rahmawati RB, Widiyatno, Hardiwinoto S, Budiadi, Nugroho WD, Wibowo A, Rodiana D. 2022. Effect of spacing on growth, carbon sequestration, and wood quality of 8-year-old clonal teak plantation for sustainable forest teak management in Java Monsoon Forest. Biodiversitas 23: 4180-4188. Lowland monsoon forest dominated by teak was one of the tropical forest types that can contribute to producing wood production, carbon storage, reduction of emissions, and other ecosystem services. Increasing teak forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The tree volume results in the current study concurred with those reported by Goh et al (2013) in Sabah, Khanduri et al (2008) in India and Rahmawati et al (2022) in Indonesia, who examined the growth and volume production of teak provenances at ages in the range 8-11 yr. These studies revealed similar mean value ranges in volume production among different teak provenances.…”
Section: Volumesupporting
confidence: 91%
“…The tree volume results in the current study concurred with those reported by Goh et al (2013) in Sabah, Khanduri et al (2008) in India and Rahmawati et al (2022) in Indonesia, who examined the growth and volume production of teak provenances at ages in the range 8-11 yr. These studies revealed similar mean value ranges in volume production among different teak provenances.…”
Section: Volumesupporting
confidence: 91%
“…The density of teak stands had a significant effect on the diameter of the canopy [39]. The width of the canopy can be used to predict the sunlight that is passed by the trees or that is blocked and intercepted in the canopy of a stand [40].…”
Section: Resultsmentioning
confidence: 99%
“…Clonal teak plantations were developed to produce timber for construction, with high diameter growth as one of the requirements. Wide spacing increases diameter growth and increases the heartwood percentage, although not significantly (Rahmawati et al, 2022). However, wide spacing reduces the bole height, so it needs to be accompanied by pruning maintenance (Rahmawati et al, 2021).…”
Section: Implication For Sustainable Clonal Teak Plantation and Susta...mentioning
confidence: 96%
“…It is due to high thinning intensity that can reduce the number of trees per hectare. Stand density affects diameter growth and volume produced per unit area(Vigulu et al, 2019;Rahmawati et al, 2022).Thinning at 25% intensity significantly increased diameter growth while providing a high volume per hectare. Thinning is the principal aspect of silviculture to produce better-quality logs at the end of the cycle(Stewart et al, 2020;Seta et al, 2021).…”
mentioning
confidence: 99%